2019
DOI: 10.1111/bjso.12315
|View full text |Cite
|
Sign up to set email alerts
|

Dirty jobs and dehumanization of workers

Abstract: The present study aims at expanding research on dehumanization in the work domain by exploring laypeople's dehumanizing perceptions towards stigmatized workers. Starting from Hughes’ (1951, Social psychology at the crossroads, Harper & Brothers, New York; Ashforth & Kreiner, 1999, Academy of Management Review, 24, 413) concept of ‘dirty work’, the present research aims to demonstrate that the different types of occupational taint elicit distinct dehumanizing images of certain occupational groups. Employing a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 56 publications
4
43
0
2
Order By: Relevance
“…In parallel, Andrighetto, Baldissarri, and Volpato (2017;see also Baldissarri et al, 2017; 2017 for a review) revealed that (factory) workers performing subordinate activities characterized by repetitive movements, fragmented activities, and dependence on machines were objectified by laypeople -that is, perceived as instrument-like (vs. a human being) and as less able to experience human mental states. In this respect, by integrating our findings with previous research (e.g., Andrighetto et al, 2017;Valtorta et al, 2019), it is plausible to think that objectification and biologization should differently apply to distinct tainted occupational categories. On the one hand, objectification seems to be related to the work activities.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In parallel, Andrighetto, Baldissarri, and Volpato (2017;see also Baldissarri et al, 2017; 2017 for a review) revealed that (factory) workers performing subordinate activities characterized by repetitive movements, fragmented activities, and dependence on machines were objectified by laypeople -that is, perceived as instrument-like (vs. a human being) and as less able to experience human mental states. In this respect, by integrating our findings with previous research (e.g., Andrighetto et al, 2017;Valtorta et al, 2019), it is plausible to think that objectification and biologization should differently apply to distinct tainted occupational categories. On the one hand, objectification seems to be related to the work activities.…”
Section: Discussionsupporting
confidence: 76%
“…Disgust is widely regarded as an innate and a highly unmodifiable emotion that deeply shapes how people react towards others (Rozin, Haidt, & McCauley, 2008;Russel & Giner-Sorolla, 2013). Accordingly, a large amount of social psychological literature (see, e.g., Buckels & Trapnell, 2013;Hodson & Costello, 2007) has shown that disgust is a rel- Valtorta, R. R., et al (2019). The Dirty Side of Work: Biologization of Physically Tainted Workers.…”
Section: Disgust and Dehumanizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The denial of humanness to others is a common phenomenon that occurs in the work domain (e.g., Christoff, 2014;Valtorta, Baldissarri, Andrighetto, & Volpato, 2019). Among the different forms of dehumanization, objectification is perhaps the most relevant in the capitalistic scenario (e.g., Cheney & Carroll, 1997;Islam, 2012;Shields & Grant, 2010;Volpato et al, 2017).…”
Section: Workers' Self-objectificationmentioning
confidence: 99%